Implementation of PSAK No. 14 On Production Support Inventory: A Case Study of Cost Control at PT SINAR HALOMOAN - Martua Hsb, Rahmat; Syafina, Laylan; Nasution, Yenni Samri Juliati (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study aims to explain the implementation of Financial Accounting Standards Statement (PSAK) No. 14 on Inventory in the context of cost control in production support activities at PT Sinar Halomoan. PSAK No. 14 regulates the accounting treatment of inventory, including recognition, measurement, recording, and presentation in financial statements. This study uses a qualitative descriptive approach with a case study method, where data is collected through in-depth interviews, internal company documentation, and direct observation of the production process and inventory recording. The results of the study indicate that PT Sinar Halomoan has implemented PSAK No. 14 in recording raw material and work-in-process inventory, but there are still several obstacles in real-time recording and cost control due to limitations of the accounting information system. The implementation of PSAK No. 14 has consistently been proven to be able to increase the efficiency of production cost control, especially through improvements in calculating Cost of Goods Sold and controlling inventory depreciation and loss. Recommendations for this study include improving the integration of training and employee information systems so that accounting standards can be applied optimally throughout the production line.